Cluster Coordination and Photoluminescence Properties of alpha-Ag2WO4 Microcrystals - Cavalcante, L. S. [UNESP]; Almeida, M. A. P.; Avansi, W. [UNESP]; Tranquilin, R. L.; Longo, Elson [UNESP]; Batista, N. C.; Mastelaro, V. R.; Siu Li, M. (Amer Chemical Soc, 2012)
In this paper, we report our initial research to obtain hexagonal rod-like elongated silver tungstate (alpha-Ag2WO4) microcrystals by different methods [sonochemistry (SC), coprecipitation (CP), and conventional hydrothermal (CH)] and to study their cluster coordination and optical properties. These microcrystals were structurally characterized by X-ray diffraction (XRD), Rietveld refinements, Fourier transform infrared (FT-IR), X-ray absorption near-edge structure (XANES), and extended X-ray absorption fine structure (EXAFS) spectroscopies. The shape and average size of these alpha-Ag2WO4 microcrystals were observed by field-emission scanning electron microscopy (FE-SEM). The optical properties of these microcrystals were investigated by ultraviolet-visible (UV-vis) spectroscopy and photoluminescence (PL) measurements. XRD patterns and Rietveld refinement data confirmed that alpha-Ag2WO4 microcrystals have an orthorhombic structure. FT-IR spectra exhibited four IR-active modes in a range from 250 to 1000 cm(-1). XANES spectra at the W L-3-edge showed distorted octahedral [WO6] clusters in the lattice, while EXAFS analyses confirmed that W atoms are coordinated by six O atoms. FE-SEM images suggest that the alpha-Ag2WO4 microcrystals grow by aggregation and the Ostwald ripening process. PL properties of alpha-Ag2WO4 microcrystals decrease with an increase in the optical band-gap values (3.19-3.23 eV). Finally, we observed that large hexagonal rod-like alpha-Ag2WO4 microcrystals prepared by the SC method exhibited a major PL emission intensity relative to alpha-Ag2WO4 microcrystals prepared by the CP and CH methods.